Lomonosov Ridge off Greenland II (LOMROG II) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during July 31 through September 9 2009 - Lomonosov Ridge off Greenland II - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during July 31 through September 9 2009. - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
The LOMROG II expedition was carried out in the summer of 2009 by the Danish Continental Shelf Project in cooperation with the Swedish Polar Research Secretariat and the Swedish Maritime Administration.
The expedition was a follow-up to LOMROG, which was conducted in 2007.
The Swedish icebreaker Oden served as the research platform, while the actual research areas was selected based on the prevailing ice situation, particularly in the area around the North Pole.
In 2009 Oden operated without the assistance of another icebreaker. The expedition focused on the areas around the North Pole, although the area northeast of Greenland also was included. The researchers were particularly interested in the Lomonosov Ridge, a mountain ridge on the ocean floor. To break through the nearly impenetrable icepack, Oden was assisted by one of the world’s most powerful icebreakers, the Russian 50 Let Pobedy.The Danish researchers mainly worked on the Continental Shelf Project, which is affiliated with the UN Convention on the Law of the Sea (UNCLOS) regarding national claims to the ocean floor. Using advanced multi-beam 3D echo sounding, seismology, and water and sediment samples, the researchers gathered information about the appearance and structure of the ocean floor. A group of marine geologists from Stockholm University also took part in the Danish project.

A sequence of sediment cores was collected from the slope of the Lomonosov Ridge as part of a project called ”Reconstructing Central Arctic Ocean Paleoceanography Using Sediment Cores from the Lomonosov Ridge”. The sediment cores could provide answers to questions about how the dynamics of the inland ice sheets have affected the global climate.

The expedition started and ended in Longyearbyen in Svalbard.

Purpose:

The study’s purpose was to collect meteorological, oceanographic and ship data during the Danish-Swedish expedition Lomonosov Ridge off Greenland II.

These data were collected onboard the icebreaker Oden during the Lomonosov Ridge off Greenland II (LOMROG II) expedition 2009 and are published by the Swedish Polar Research Secretariat.
Obviously erroneous data have been omitted. No other processing of the data has been undertaken.

The dataset contains the following files:
Lomrog2.txt - Main file containing data as described below.
Lomrog2_overview.txt - File containing an hourly data excerpt from the full data file above.
Lomrog2_depth.txt - File contains water depth. (Different time resolution compared to main file)
Lomrog2.shp - Shape file of LOMROG II route.
Lomrog2.kml - Google Earth file of LOMROG II route.

Under sommaren 2009 genomfördes expeditionen LOMROG II (Lomonosov Ridge off Greenland) av det danska Kontinentalsokkelprojektet i samarbete med Polarforskningssekretariatet och Sjöfartsverket. Expeditionen var en uppföljning av LOMROG, som genomfördes år 2007.

Den svenska isbrytaren Oden fungerade som forskningsplattform och forskningsområdena valdes beroende på den rådande issituationen, framför allt i området kring Nordpolen.

2009 opererade Oden utan assistans från annan isbrytare. I fokus låg områdena kring Nordpolen, men även området nordost om Grönland var aktuellt. Särskilt Lomonosovryggen, en bergsrygg på havsbottnen, tilldrog sig forskarnas intresse. De danska forskarna arbetade främst inom Kontinentalsokkelprojektet, som har koppling till FN:s havsrättskonvention om nationers anspråk på havsbotten. Med hjälp av ett avancerat flerstråligt 3D-ekolod, seismik och provtagning av sediment och vatten samlade forskarna information om havsbottnens utseende och uppbyggnad. En grupp maringeologer från Stockholms universitet deltog inom det danska projektet. En sekvens av sedimentkärnor togs från Lomonosovryggens sluttning inom projektet ”Arktiska oceanens historia rekonstruerad med hjälp av sedimentkärnor från centrala Lomonosovryggen”. Sedimentkärnorna kan bland annat ge svar på frågor om hur inlandsisarnas dynamik har påverkat det globala klimatet.

Expeditionen startade och avslutades i Longyearbyen på Svalbard.

Syfte:

Studiens syfte var att samla meteorologiska och oceanografiska data samt skeppsdata under den dansk-svenska expeditionen Lomonosov Ridge off Greenland II.

These data were collected onboard the icebreaker Oden during the Lomonosov Ridge off Greenland II (LOMROG II) expedition 2009 and are published by the Swedish Polar Research Secretariat.
Obviously erroneous data have been omitted. No other processing of the data has been undertaken.

The dataset contains the following files:
Lomrog2.txt - Main file containing data as described below.
Lomrog2_overview.txt - File containing an hourly data excerpt from the full data file above.
Lomrog2_depth.txt - File contains water depth. (Different time resolution compared to main file)
Lomrog2.shp - Shape file of LOMROG II route.
Lomrog2.kml - Google Earth file of LOMROG II route.
Lomonosov Ridge off Greenland II (LOMROG II) - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden från 31 juli till 9 september 2009 - Lomonosov Ridge off Greenland II - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during July 31 through September 9 2009.
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; CONDUCTIVITY; OCEAN TEMPERATURE; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö